Model Hubungan Kompensasi Non-Financial dan Komitmen Karyawan: Peran Pendidikan Sebagai Pemoderasi - Sitti Marijam Thawil (LPMP Imperium, 2019)
This study aims to determine the effect of non-financial rewards on organizational commitment with education as a moerator. This research is included in the type of survey research, namely research whose information is collected from respondents using a questionnaire. As much as 55 respondents were involved in the survey, and the data were analyzed by moderating regression. This study concludes that non-financial rewards (career development, development opportunities and recognition) are tools that management can use to increase commitment